Rotary Cement Kiln Simulator (RoCKS): integrated modeling of pre-heater, calciner, kiln and clinker cooler - Mujumdar, Kaustubh S.; Ganesh, K. V.; Kulkarni, Sarita B.; Ranade, Vivek V. (Chemical Engineering Science, 2007)
This paper presents an integrated reaction engineering based mathematical model for clinker formation in cement industry. Separate models for pre-heater, calciner, rotary kiln and cooler were initially developed and coupled together to build an integrated simulator. Appropriate models for simulating gas-solid contact and heat transfer in pre-heaters were developed. Calciner was modeled by considering simultaneous combustion of coal particles and calcination of raw meal. Complex heat transfer and reactions (solid-solid, gas-solid and homogeneous reactions in gas phase) in rotary kiln were modeled using three sub-models coupled to each other. Solid-solid reactions in the bed region of the kiln were modeled using pseudo-homogeneous approximation. Melting of solids in the bed and formation of coating within the kiln were accounted. Clinker cooler was simulated by developing a two-dimensional model to capture cross-flow heat transfer between air and hot clinkers. The individual models were coupled with each other via mass and energy communication through common boundaries. The coupled model equations were solved iteratively. The model predictions agree well with the observations and experience from cement industry. The model was used to gain better understanding of influence of operating conditions on energy consumption in cement plant. Several ways for reducing energy consumption were computationally investigated. The integrated model, the developed software RoCKS (for Rotary Cement Kiln Simulator) and results presented here will be useful for enhancing our understanding and for enhancing the performance of clinker manufacturing. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: cement; energy consumption; reaction engineering model

Reaction engineering of urea alcoholysis: alkyl carbamates - Mote, Dhananjay R.; Ranade, Vivek V. (Indian Journal of Chemical Technology, 2017)
Urea alcoholysis is a reversible reaction generating alkyl carbamate and ammonia as products. The reaction can be performed non-catalytically or in presence of catalyst. The first step in Reaction engineering analysis is to finalize the reactor configuration. In this case it is important to determine the necessity of reactive separation (simultaneous reaction and separation). This has been addressed by first establishing the reversibility of the reaction through theoretical and experimental investigation. Based on this analysis, an experimental setup comprising tubular reactor and a separator has been built. Experiments have been performed for different alcohols at different flow rates and temperatures. The experimental data is used to establish kinetic parameters. Systematic reaction engineering analysis based on multi-stage ideal reactors with and without simultaneous mass transfer is then carried out in terms of three dimensionless numbers. The analysis presented in this work can be readily applied to a general class of reversible reactions with volatile products and the methodology can be used to develop and design reactors for them. The approach and results presented here will be useful to establish optimal reactor configuration and design for urea alcoholysis reactions.